2017
DOI: 10.1530/ec-17-0104
|View full text |Cite
|
Sign up to set email alerts
|

GNRHR biallelic and digenic mutations in patients with normosmic congenital hypogonadotropic hypogonadism

Abstract: ObjectiveNormosmic congenital hypogonadotropic hypogonadism (nCHH) is a rare disorder characterised by lack of pubertal development and infertility, due to deficient production, secretion or action of gonadotropin-releasing hormone (GnRH) and, unlike Kallmann syndrome, is associated with a normal sense of smell. Mutations in the GNRHR gene cause autosomal recessive nCHH. The aim of this study was to determine the prevalence of GNRHR mutations in a group of 40 patients with nCHH.DesignCross-sectional study of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This is a high prevalence when compared to the contribution of other genes that have been historically considered as priorities in the genetic study of CHH, namely the ANOS1 ( KAL1 ), FGFR1 , and GNRHR genes 26 . Indeed, previous studies in the Portuguese population have shown that the ANOS1 ( KAL1 ), FGFR1 , and GNRHR genes are mutated in only 7.1%, 12.0%, and 12.5% of cases, respectively 1416 . Studies in other populations have also shown an important contribution of CHD7 mutations in the aetiology of CHH, with frequencies ranging from 5.2% to 19.0%, of cases 611 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a high prevalence when compared to the contribution of other genes that have been historically considered as priorities in the genetic study of CHH, namely the ANOS1 ( KAL1 ), FGFR1 , and GNRHR genes 26 . Indeed, previous studies in the Portuguese population have shown that the ANOS1 ( KAL1 ), FGFR1 , and GNRHR genes are mutated in only 7.1%, 12.0%, and 12.5% of cases, respectively 1416 . Studies in other populations have also shown an important contribution of CHD7 mutations in the aetiology of CHH, with frequencies ranging from 5.2% to 19.0%, of cases 611 .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic deoxyribonucleic acid (DNA) was extracted from peripheral blood leucocytes using previously described methods 13 . Patients had already been screened for mutations in the ANOS1 , FGFR1 and GNRHR genes, resulting in the discovery of three mutations in ANOS1 14 , six mutations in FGFR1 15 and six mutations in GNRHR 16 . All 50 patients were subsequently screened for mutations in the CHD7 gene by polymerase chain reaction (PCR) amplification of the coding exons and exon-intron boundaries, and bi-directional sequencing using CEQ DTCS sequencing kit (Beckman Coulter, Fullerton, CA, USA) and an automated capillary DNA sequencer (GenomeLab TM GeXP, Genetic Analysis System, Beckman Coulter).…”
Section: Methodsmentioning
confidence: 99%
“…Pathological changes in any of these processes can lead to CHH. To date, over 30 genes have been found to be associated with CHH and many encode receptor-ligand pairs, such as FGFR1 (OMIM 136350) and FGF8 (OMIM 600483), GNRHR (OMIM 138850) and GNRH1 (OMIM 152760), TACR3 (OMIM 162332) and TAC3 (OMIM 162330), KISS1R (OMIM 604161) and KISS1 (OMIM 603286), as well as PROKR2 (OMIM 607123) and PROK2 (OMIM 607002) (7,8,9,10,11,12,13). Furthermore, disruption in the dynamic remodelling of the cell's cytoskeleton during migration of GnRH neurons may also result in CHH (14,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of HH that are caused by GNRHR variants, are biallelic, consistent with an autosomal recessive mode of inheritance. However, digenic inheritance of HH has also been reported due to a monoallelic GNRHR variant together with monoallelic variants in other genes causing HH including PROKR2, FGFR1 , and WDR11 ( 26 28 ). Basal plasma concentrations of LH and FSH were low and did not increase after GnRH test, while the plasma estradiol concentration was prepubertal.…”
Section: Resultsmentioning
confidence: 99%